Exploring the development of an energy efficiency one-stop shop - Mendes, Miguel Projecto (2022)
Energy is an essential pillar for any economy. In Europe, energy consumption has been gaining prominence as energy costs increase, especially in the most consuming sectors such as transport, industry and buildings. With the residential sector accounting, on average, for more than a quarter of total final energy consumption, makes it a key sector for the energy transition. In line with several recent policies and strategies, many European countries have created methods to implement on-site measures that help the population and ensure a fair energy transition, encourage the improvement of energy performance on residential buildings and reduce the population's vulnerability to energy poverty. This thesis's objectives consist on developing a methodological approach to study the implementation of an energy efficiency One-Stop Shop to address energy poverty. This approach consists in implementing a mobile One-Stop Shop for Energy Efficiency in two locations in Setúbal, Portugal using twelve simple steps. This mobile unit, made from a used shipping container for portability, allows to concen- trate all relevant information needed to help users reduce their energy bills and to improve energy efficiency at home. Approximately six months after the implementation and after ana- lysing the data collected by the survey, it was possible to verify that users from the target group were the most difficult to reach. Was registered a higher incidence of middle-class users look- ing for public funding, instead of users in more severe energy poverty situations per se. The majority of the surveyed population had interest in renovating their homes to improve their energy efficiency but were looking for available governmental grants to help with investment costs.